The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12031-013-9964-0
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol Protects Against Oxidative Stress-Mediated Neural Cell Damage by Modulating Mitochondrial Dysfunction and PI3K/Akt Signaling

Abstract: Magnolol, an orally available compound from Magnolia officinalis used widely in traditional herbal medicine against a variety of neuronal diseases, possesses potent antioxidant properties and protects the brain against oxidative damage. The aim of the work is to examine the protective mechanisms of magnolol on human neuroblastoma SH-SY5Y cells against apoptosis induced by the neurotoxin acrolein, which can cause neurodegenerative disorders by inducing oxidative stress. By investigating the effect of magnolol o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 41 publications
2
39
0
1
Order By: Relevance
“…Dong et al . reported that magnolol protected SH-SY5Y cells against acrolein-induced neural cell damage through regulating PI3K/AKT/FOXO1 signaling pathway55. In our results, the PTS-upregulated SIRT1 expression and phosphorylation of FOXO3 were attenuated by the pretreatment of LY294002 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Dong et al . reported that magnolol protected SH-SY5Y cells against acrolein-induced neural cell damage through regulating PI3K/AKT/FOXO1 signaling pathway55. In our results, the PTS-upregulated SIRT1 expression and phosphorylation of FOXO3 were attenuated by the pretreatment of LY294002 (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Whether apoptosis or necrosis ensues after acrolein exposure appears to be related to dose and cell type. In regards to activation of caspases as part of the mitochondrial death pathway, it was shown that apoptosis in human cells is caspase-dependent, as demonstrated in human neuroblastoma cells (Dong et al 2013) and in A549 lung cells (Roy et al 2009). It was suggested that the activation of certain caspases may arise from a partial inhibition of their active site cysteine residue through direct alkylation by acrolein (Kern and Kehrer 2002).…”
Section: Mie: Protein Alkylationmentioning
confidence: 99%
“…Decreased levels of SIRT1 activity can be the result of apoptotic pathways associated with p38 (267) and c-Jun N-terminal kinase -1 (JNK1) (46) as well as caspase degradation of SIRT1 (268) that can then lead to further activation of caspases (268, 269). As previously described, pathways such as WISP1 prevent SIRT1 degradation and block caspase activation that would otherwise lead to the degradation of SIRT1 (174, 270272). …”
Section: Sirt1 and Dmmentioning
confidence: 80%